Actividad antibacteriana del extracto hidroalcohólico de Averrhoa Carambola L. (Carambola) frente a cepas de Staphylococcus Epidermidis - Valladares Quispe, Guisenia Mayumi; Soria Avelino, Esther Irene (Universidad Privada de Huancayo Franklin Roosevelt, 2021)
Objetivo: Determinar la actividad antibacteriana del extracto hidroalcohólico de Averrhoa carambola L. (Carambola) frente a la cepa Staphylococcus epidermidis. Metodología: Estudio analítico, experimental, transversal de nivel explicativo, prospectivo. Resultados: Los resultados evidenciaron efecto antibacteriano del extracto hidroalcohólico frente a Staphylococcus epidermidis, presentando halos de inhibición promedio de 13,08 ± 0,43 mm y 9,82 ± 0,38 mm en las concentraciones al 100 y 50% respectivamente y 15,06 ± 0,78 mm en el control positivo. Conclusión: El extracto hidroalcohólico de carambola tiene actividad antibacteriana frente a Staphylococcus epidermidis

Objective: To determine the antibacterial activity of the hydroalcoholic extract of Averrhoa carambola L. (Carambola) against Staphylococcus epidermidis strain. Methodology: Analytical, experimental, cross-sectional, prospective, explanatory level study. Results: The results showed antibacterial effect of the hydroalcoholic extract against Staphylococcus epidermidis, presenting average inhibition halos of 13.08 ± 0.43 mm and 9.82 ± 0.38 mm in the concentrations at 100 and 50%, respectively, and 15.06 ± 0.78 mm in the positive control. Conclusion: The hydroalcoholic extract of carambola has antibacterial activity against Staphylococcus epidermidis
Antibacterial activity of Averrhoa Carambola L. (Carambola) hydroalcoholic extract against Straphylococus Epidermidis strains
Keywords: Averrhoa carambola; Staphylococcus epidermidis; Antibacteriano; Halo de inhibición; https://purl.org/pe-repo/ocde/ford#3.01.05